Novel Entamoeba findings in nonhuman primates - Elsheikha, Hany M.; Regan, Carl S.; Clark, C. Graham (Elsevier, 2018)
In addition to well-known human-infecting species, Entamoeba species not found in humans have been identified recently in nonhuman primates (NHPs). Importantly, it has become clear that the organism identified as Entamoeba histolytica in NHPs is usually a distinct species, Entamoeba nuttalli. Many DNA-based stool surveys use species-specific detection methods and so may miss the full range of Entamoeba species present. In addition, authors may be using the same species name to describe distinct organisms. These various shortcomings may not be obvious to readers. In this review, we clarify the relationships between Entamoeba species’ names based on morphological and molecular data, and highlight gaps in recently published data on Entamoeba species in wild NHPs resulting from the use of variable methodology.